Acceptability, conflict, and support for coastal resource management policies and initiatives in Cebu, Philippines - Allegretti, Arren Mendezona, author; Cottrell, Stuart, advisor; Manfredo, Michael J., advisor; Vaske, Jerry J., 1951-, committee member; Thompson, Jessica Leigh, committee member; Taylor, Peter Leigh, 1959-, committee member (Colorado State University. Libraries, 2010)
Efforts to address the decline of coastal and habitat resources by Coastal Resource Management (CRM) initiatives are done via application of frameworks such as Integrated Coastal Management (ICM) and Ecosystem Based Management (EBM). Recent literature stresses the necessity to complement biological monitoring with social science monitoring of coastal areas by applying social science concepts in CRM. Linkages between social science concepts such as a conflict, acceptance, and public support for CRM with research themes of governance, communities, and socioeconomics are crucial for advancing our understanding of the social success of CRM initiatives. In light of the scholarly and applied need, this thesis focuses on analyzing stakeholder perceptions, conflict, and public support for CRM policies and initiatives in Southern Cebu, Philippines. In particular, this thesis examines stakeholder attitudes and normative beliefs of CRM scenarios, and links these perceptions with public support of CRM policies and initiatives implemented at the levels of the community, municipality, and the Marine Protected Area (MPA) Network. This thesis presents two manuscripts applying qualitative and quantitative social science methods for understanding stakeholder perceptions of conflict, acceptance, and public support for CRM policies. The first manuscript applies the Potential for Conflict Index (PCI2), a statistic that graphically displays the amount of consensus and the potential for conflict to occur in a CRM scenario. Specifically, the PCI2 displays fishers' normative beliefs concerning their consensus and acceptability of CRM policies and initiatives. Face-to-face interviews with fishers serve as data for calculating the PCI2. This manuscript compares fishers' normative beliefs concerning their evaluations of CRM policies among the municipalities of Oslob, Santander, and Samboan in Southern Cebu. Overall, fishers' differing evaluations reflects the way CRM is implemented and enforced in each of these municipalities. Fishers' evaluations allow local governments to understand acceptability of CRM policies as well as make better management decisions concerning policy compliance, consensus for policies, and conflict within a municipality. The second manuscript of this thesis applies qualitative conflict mapping methods to the investigation of institutional conflict and accountability within a coastal municipality in Southern Cebu. Using in-depth interviews, conflict mapping methods enables the analysis of stakeholder attitudes of institutional conflict and accountability for CRM. This manuscript investigates institutional relationships among stakeholders accountable for CRM. Lastly, this manuscript examines how institutional relationships and stakeholder perceptions affect CRM at the community, municipality, and the MPA Network. The interpretive analysis reveals that conflicts concerning institutional accountability for CRM are often at the root of problems for implementing and enforcing coastal management initiatives and policies within the different communities of the municipality. Theoretical implications of this thesis include the application of normative theories and qualitative conflict analysis frameworks for understanding stakeholder perceptions of conflict and public support for CRM initiatives. Managerial applications of this thesis include the use of quantitative (PCI2) and qualitative (conflict mapping) social science monitoring methods applicable for understanding social science concepts such as stakeholder perceptions, conflict, and public support for CRM policies and initiatives. Future studies could include the combined use of PCI2 and conflict mapping as complementary research methods for investigating collaborative local government decision making processes crucial for the social success of CRM initiatives.